Progress towards a circular economy in materials to decarbonize electricity and mobility. (March 2021) - Mulvaney, Dustin; Richards, Ryan M.; Bazilian, Morgan D.; Hensley, Erin; Clough, Greg; Sridhar, Seetharaman
Abstract: Over 90% of the global economy continues to use natural resources unsustainably. The linear "take-make-toss" approach to materials use still prevails over circular economy and industrial ecology ideas in practice. The shift to renewable energy is one step towards building an economy on more circular material flows. But the materials needed to decarbonize electricity and mobility are supplied by mining and extractives industries, places where impacts from natural resource extraction can be most severe. Manufacturers of wind turbines, photovoltaics, batteries and vehicles—critical technologies to the clean energy transition—still primarily rely on feedstocks and inputs from natural resources as opposed to waste for processing and production. Similarly, robust and complete end-of-life (EoL) management strategies are not well developed for these materials. This review synthesizes progress towards a circular economy—reducing impacts from resource extraction, metallurgy, manufacturing, and waste disposal, and resource recovery—in key materials needed to decarbonize electricity and mobility. Efforts to manufacture by principles of sustainable design to reclaim the recycling value of EoL product waste are complicated by new materials and increasingly complex composites. Dialog and collaboration about trends in materials use and waste flows that span extractive industry scientists and professionals to product designers and recyclers will be critical to spurring the technological and policy innovations needed to encourage more progress. Highlights: Over 90% of the global economy continues to function unsustainably. Materials produced largely lack viability or end-of-life disposal strategy. We evaluate progress towards sustainable materials use in key sectors.